Exploring the retirement from sport decision-making process based on the transtheoretical model - Park, S.; Tod, D.; Lavallee, D. (Psychology of Sport and Exercise, 2012)
Objectives: The purpose of this study was to complement and extend the current knowledge of the particular stages of athletes` career transition process through employing the transtheoretical model (Prochaska & DiClemente, 1984) as a theoretical framework. More specifically, the current study aimed to explore Korean elite tennis players` career transition process through focusing on their retirement decision-making process, including their cognitive and behavioral changes and internal and external influences for their decisions during the final stages of their sport careers and the retirement decision-making process. Design: We employed focus groups. Methods: A total of 12 participants took part in one of three focus groups (i.e., four current players, five retired players, and three coaches) that focused on the process of athletes' retirement decision-making. All participants (seven males and five females; Mean age = 31.25, SD = 3.49 years) were either current or former Korean elite-level tennis players. The data were thematically content analyzed. Results: The results revealed three themes: (a) readiness for retirement, (b) psychological and emotional responses during the decision-making process, and (c) coping strategies; and showed that athletes` decision-making at the end of their sports careers is a dynamic process, accompanied by various emotional responses requiring different coping strategies at different stages. Conclusion: Findings indicated that the transtheoretical model helped to explain athletes` decision-making in retiring from sport and suggested to the need to provide different interventions at different stages. Identifying detailed aspects of readiness for retirement and examining the effectiveness of interventions grounded in the transtheoretical model are recommended as future research directions.